ANALISIS PERBEDAAN BAHASA INDONESIA DAN SASTRA INDONESIA DALAM INSTITUSI PENDIDIKAN SEBAGAI UPAYA PENINGKATAN PENGETAHUAN BAGI MASYARAKAT INDONESIA - Gina Syabani Yuda; Akhmad Khuzairi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of knowledge often leads the public to view Indonesian Language and Indonesian Literature as two similar concepts, even though both have different meanings and interpretations when examined in depth. This study aims to analyze the differences in the fundamental concepts between Indonesian Language and Indonesian Literature, as well as how both are implemented within Indonesian society, particularly in the context of educational institutions. Conceptually, Indonesian Language is defined as the national and official language of the country, functioning as the primary tool of communication, a marker of national identity, and a medium for the development of science and technology. Meanwhile, Indonesian Literature refers to human expressions (in the form of poetry, prose, and drama) that combine experience and imagination into an aesthetic and meaningful linguistic form, functioning as a medium for social reflection, cultural expression, and moral education. Both are interconnected in shaping the cultural and intellectual identity of the nation. Implementation in society shows that Indonesian Language serves as a unifying tool among ethnic groups and as a medium of formal and informal communication, reinforced through policies, curricula, and literacy initiatives. Indonesian Literature is implemented as a medium for character education, a reflection of social and cultural values, and a component of cultural literacy. Despite challenges such as linguistic diversity and the dominance of informal or colloquial language, there are significant opportunities to strengthen implementation through character education, technological integration, and inclusive policies. The conclusion of this study is that understanding the conceptual and functional differences between Indonesian Language and Indonesian Literature is essential to minimize public misconceptions. Strengthening Indonesian language literacy and connecting Indonesian Literature with community life and popular culture are key recommendations for reaching all levels of society, including the younger generation in the digital sphere.